Republic of Serbia : Staff Report for the 2019 Article IV Consultation and Second Review under the Policy Coordination Instrument-Press Release; Staff Report; Information Annex; Staff Statement; and Statement by the Executive Director for Republic of Serbia. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Republic of Serbia's 2019 Article IV Consultation and Second Review Under the Policy Coordination Instrument. Serbia's macroeconomic performance, supported by the Policy Coordination Instrument, has been strong. Growth has been robust, public debt is declining, employment is rising, the financial sector is sound, and inflation is low. Strong fiscal performance continues, facilitating higher capital spending and a reduction of the tax burden on labor as well as faster debt reduction. Continued strong program implementation and determined structural reforms are important to address the challenges and accelerate income convergence with the EU. Fiscal performance has been strong, while important reforms took place toward modernization of the tax administration and privatization of the largest state-owned bank. Stronger commitment to the implementation of planned structural reforms is needed to boost potential growth and improve the private investment climate. However, Serbia remains vulnerable to spillovers from external developments, including weaker-than-expected growth in key trading partners.